The Impact of Internal Environment of Working on the firms performance (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2013)
Research on monetary evaluation of the impact of internal environment on firms performance always remains of importance interest. However, the validity of the results depends on the methods of evaluation and measurement used. The aim of this study is to evaluate the degradation of the firms performance as consequence of the following two aspects: occupational accidents and injuries and the pollution of the work environment. The first part of this paper presents a brief review of the theoretical concepts, which illustrate the relationship between the work environment and the firms performance. The fieldwork constitutes the central arguments of the second part. The method used for the evaluation of the health damages. The results obtained stress the importance of the Health and safety issues on the performance of the firm.